The formula for exponential growth is P =Ae^kt
P = new population
A = starting population
k is a constant
and t is number of years.
e is a logarithm function
using the 2 known years
we know 2002-1990 = 12 years
the population in 2002 was 63 million, population in 1990 was 59 million
so using the above equation we can solve for k:
63 = 59e^k12
divide both sides by 59:
63/59 = e^k12
1.06779 = e^k12
find logorithm of left side to get rid of the e on the right side:
ln 1.06779 = k12
0.06559 = k12
divide both sides by 12 for k:
k = 0.06559 / 12 = 0.00546644
now we want to find population in 2018
2018 - 1990 = 28 years
so now t = 28 using the same formula we have:
P = 59e^(0.00546644*28)
P = 68.758 million
rounded to nearest million = 69 million people